Impact of the development of an endoscopic eradication program for Barrett’s esophagus with high grade dysplasia or early adenocarcinoma on the frequency of surgery - Chilukuri, Prianka; Gromski, Mark A.; Johnson, Cynthia S.; Ceppa, Duy Khanh P.; Kesler, Kenneth A.; Birdas, Thomas J.; Rieger, Karen M.; Fatima, Hala; Kessler, William R.; Rex, Douglas K.; Al-Haddad, Mohammad; DeWitt, John M. (Endoscopy International Open, 2018)
Background and aims The impact of the advent of an institutional endoscopic eradication therapy (EET) program on surgical practice for Barrett’s esophagus (BE)-associated high grade dysplasia (HGD) or suspected T1a esophageal adenocarcinoma (EAC) is unknown. The aims of this study are to evaluate the different endoscopic modalities used during development of our EET program and factors associated with the use of EET or surgery for these patients after its development.Methods Patients who underwent primary endoscopic or surgical treatment for BE-HGD or early EAC at our hospital between January 1992 and December 2014 were retrospectively identified. They were categorized by their initial modality of treatment during the first year, and the impact over time for choice of therapy was assessed by multivariable logistic regression.Results We identified 386 patients and 80 patients who underwent EET and surgery, respectively. EET included single modality therapy in 254 (66 %) patients and multimodal therapy in 132 (34 %) patients. Multivariable logistic regression showed that, for each subsequent study year, EET was more likely to be performed in patients who were older (P = 0.0009), with shorter BE lengths (P < 0.0001), and with a pretreatment diagnosis of HGD (P = 0.0054) compared to surgical patients. The diagnosis of EAC did not increase the utilization of EET compared to surgery as time progressed (P = 0.8165).Conclusion The introduction of an EET program at our hospital increased the odds of utilizing EET versus surgery over time for initial treatment of patients who were older, had shorter BE lengths or the diagnosis of BE-HGD, but not in patients with EAC.